The Use of Physical Strength in Children's Education: Learning from Indonesian Court's Judgments - Eva Achjani Zulfa; Artha Febriansyah; Jelang Ramadhan; Imam Khomaeni Hayatullah (Sriwijaya Law Review, 2024)
This article explores the limitations of using physical force in educating children in Indonesia. It examines the prevalence of violence by parents and teachers in education. Increased public awareness and concern for children's rights have made the use of violence in education a taboo. This research uses a qualitative method with secondary data using literature and analysing court decisions from the human rights perspective. This study aims to determine the limits of tolerance for violence and corporal punishment. The court decisions have been taken as the data to be analysed from various locations where decisions have been issued were taken into consideration to depict the similarities and differences in deciding matters related to corporal punishment towards children. This article examines historical, cultural, and religious factors that influence the use of physical force, including interpretations of Islamic teachings. This paper also presents arguments for and against corporal punishment as an educational tool. This research sheds light on the complexities surrounding the permissibility of physical force in children's education and the conflicting views in society, providing insight into evolving understandings and legal perspectives on the subject.